Integrated Assessment of Artisanal and Small-Scale Gold Mining in Ghana—Part 1: Human Health Review - Basu, Niladri (Int J Environ Res Public Health, 2015)
This report is one of three synthesis documents produced via an integrated assessment (IA) that aims to increase understanding of artisanal and small-scale gold mining (ASGM) in Ghana. Given the complexities surrounding ASGM, an IA framework was utilized to analyze economic, social, health, and environmental data, and co-develop evidence-based responses with pertinent stakeholders. The current analysis focuses on the health of ASGM miners and community members, and synthesizes extant data from the literature as well as co-authors’ recent findings regarding the causes, status, trends, and consequences of ASGM in Ghana. The results provide evidence from across multiple Ghanaian ASGM sites that document relatively high exposures to mercury and other heavy metals, occupational injuries and noise exposure. The work also reviews limited data on psychosocial health, nutrition, cardiovascular and respiratory health, sexual health, and water and sanitation. Taken together, the findings provide a thorough overview of human health issues in Ghanaian ASGM communities. Though more research is needed to further elucidate the relationships between ASGM and health outcomes, the existing research on plausible health consequences of ASGM should guide policies and actions to better address the unique challenges of ASGM in Ghana and potentially elsewhere.